Brand's country-of-origin effect on demand for hotels: An exploratory study - Zalina Zainudin; Mazhar Hallak Kantakji; Omer Bin Thabet; Nur Syairah Ani; Nursyuhadah Abdul Rahman (Contemporary Economics, 2020)
The purpose of this study is to explore the effects of a brand's country-of-origin for a hotel on its geographic markets. The globalization of tourist markets has recently increased the importance of foreign demand for most European destinations, and the role of brands in attracting foreign de- mand is growing as a consequence. The brand is one of the key assets of multinational companies in tourism. Among the several determinants of consumer brand knowledge in the global competi- tive arena, country-of-origin (COO) effects remain among the most researched. Through an explor- atory study, based on a survey of 95 branded hotels located in Italy belonging to 16 brands having USA, Spain, France and UAE as COO, we investigated the relationship between the hotel brand's COO and the top 5 geographic markets for the hotel. Our exploratory study demonstrates that in over 95% of cases the brand's COO market is one of the top 5 feeding markets for a hotel, thus in- dicating that, for a hotelier, choosing a certain hotel brand as franchisor or management company will significantly determine the geographic provenience of its hotel's guests.
Keywords: Z32; Z30; O19; 330; Hotel chains; sales performance; country of origin; brand strategy